(untitled) (Latakia University Journal -Basic Sciences Series, 2020)
The aim of this study was to evaluate the quality of groundwater in the spread area of the (Baer-Al-Bassit) Ophiolitc complex and their suitability for drinking and irrigation purposes according to the Syrian standards. Groundwater samples were collected from the wells and springs in the villages of the area (Al namlah، AlEman، Al Zaytouna، Al Fajr، Al Doha، Qarah Falah، Al Balouta، Al Daflah).Some of physical parameters were measured (temperature T،pH،electrical conductivity Ec)، And Some of chemical parameters represented by the determination of the main element ions. (Ca2 +، Mg2 + ،K +، Na +، Cl-، SO42-، HCO3-) and some heavy metals (chromium، nickel، cobalt) . The results showed that groundwater is highly influenced by the weathering of ophiolitic rocks which is slightly alkaline and shows (Mg HCO3) water type as a major type using Piper plot.The concentration of magnesium and bicarbonate ions were predominant in most water samples and exceeding maximum permissible limit according to the Syrian standards.While the concentrations of ions (Ca2+، K +، Na +) (Cl-، SO42-، NO3-) were within the limits of drinking water. Chromium ions concentration in the range (0.12 - 15.89) ppb، cobalt between (0.29 - 1.92) ppb، and nickel between (3.68 - 15.68) ppb. These concentrations were within the permissible limits except for 4 samples (Al namlah spring 1، Al namlah spring 2، Zaitouna spring، Al-Duha well) that have revealed high concentrations of nickel exceeding maximum permissible. Based on sodium hazard criteria (SAR، Na(%)، groundwater samples were suitable for irrigation، while the magnesium hazard ​​(MAR) in most of the groundwater samples were high (>50) and it may be causes damage to agricultural crops with the passage of time.